Design and construction of a test rig for grouping of tiny particles using acoustic combined oscillations - Sim Tanaka, Yusuke Melvyn (2019)
Despite the abolishment of the “Slash and Burn” agriculture by the Indonesian government, the haze from Indonesia continue to spread mainly in the South ASEAN region due to global warming. Because of this, High Efficiency Particulate Arrestance (HEPA) filters are required in major facilities such as hospitals, and these filters need to be replaced frequently. To address the high cost of replacements, conventional grade G4 pre-filter and acoustic agglomeration were studied earlier to improve the air quality of the clean rooms. The spraying of water droplets into the aerosol and construction of a spray chamber is proposed in this study. This study shows that experimental results of the agglomeration efficiency increases up to 53.4% with the addition of acoustic and spray agglomeration, as compared to acoustic agglomeration alone which is only up to 22.5%. Subsequently, a standing wave of 920Hz was utilized throughout the third and fourth parts of this project. Further studies can be done in the higher decibels and frequency of the standing waveform that can improve the efficiency of the grade G4 pre-filters.